aMMP-8 and MMP-9: Potential Biomarkers for periodontitis Progression in Patients Receiving Radiotherapy for Head and Neck Carcinoma - Ella Brandt DDS; Wendy Kaman PhD; Floris Bikker PhD; Ismo T. Räisänen DDS, PhD; Antti Mäkitie MD, PhD; Mutlu Keskin DDS, PhD; Didem Karaçetin MD; Jaana Hagström DDS, PhD; Jaana Rautava DDS, PhD; Timo Sorsa DDS, PhD (Cancer Control)
Introduction Matrix metalloproteinases (MMP)-8 and −9 are regarded as biomarkers for periodontitis. The impact of head and neck carcinoma (HNC) radiotherapy (RT) on these biomarkers remains largely unexplored. This study aims to evaluate the impact of HNC RT on the proteases from host and bacteria, and their associations with the progression of periodontitis. Methods Twenty-one patients with HNC receiving RT were included in this study. Mouthrinse samples were collected before RT (T0) and at the end of RT (T1). Periodontal examinations were conducted at T0 and one month after RT (T2). Samples were analyzed using a point-of-care kit for active (a) MMP-8, and ELISA for total (t) MMP-8, MMP-9, and interleukin (IL)-6 levels. Molecular forms of MMP-9 were assessed by gelatinolytic zymography. The activity levels of bacterial proteases, gingipain from Porphyromonas gingivalis and dentilisin from Treponema denticola , were assayed by using Fluorescence Resonance Energy Transfer (FRET) peptide substrates. Modified cumulative risk score (CRS) index was used for combinatory biomarker analysis. We evaluated the impact of RT on biomarker concentrations as well as their associations with the mean clinical attachment loss (CAL) development, categorized as either progressive (CAL ≥0.1 mm) or low/no progression (CAL <0.1 mm). Results All patients suffered from periodontitis. There were significant increases in the levels of aMMP-8, tMMP-8, aMMP-9, as well as in four modified CRS-indices due to RT ( P < 0.05), but no impact on the activities of gingipain ( P = 0.365) or dentilisin ( P = 0.620). The mean levels of aMMP-8 and tMMP-9 were associated with CAL progression ( P = 0.044, P = 0.029, respectively). Conclusion HNC RT may result in the progression of periodontitis by increased activities of MMP-8 and -9. It seems that HNC RT has little impact on the activities of the bacteria-derived proteases dentilisin and gingipain.